[tex]f =(x) = \frac{x}{4} [/tex]
[tex]fg (x) = \frac{1}{2x + 1} [/tex]
Find g(x)
![texf x fracx4 textexfg x frac12x 1 texFind gx class=](https://us-static.z-dn.net/files/d9e/c839543c78a6ee493c4bde93f23c6e47.jpg)
Answer:
g(x) = [tex]\frac{x+3}{x-3}[/tex]
Step-by-step explanation:
From the picture attached,
Given function is,
f(x) = x + 1
We have to find the value of g(x) if the composite function has been given as,
f[g(x)] = g(x) + 1 = [tex]\frac{2x}{(x-3)}[/tex]
g(x) = [tex]\frac{2x}{(x-3)}-1[/tex]
= [tex]\frac{2x-(x-3)}{(x-3)}[/tex]
= [tex]\frac{(x+3)}{(x-3)}[/tex]
Therefore, g(x) = [tex]\frac{x+3}{x-3}[/tex] will be the answer.